Association between rs1800795 polymorphisms in the interleukin-6 gene and vasculitis: A meta-analysis: IL-6 polymorphisms in vasculitis - Jung, Jae Hyun; Seok, Hongdeok; Choi, Sung Jae; Song, Gwan Gyu; Han, Youngjin (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Interleukin (IL)-6 is associated with the development and progression of vasculitis, and inhibitors of this cytokine are used to treat this disease. Polymorphisms of the promoter region of IL-6 are associated with the production and expression of IL-6. The aim of this study was to perform a meta-analysis of eligible studies to derive a precise estimate of the association between IL6 polymorphisms and susceptibility to vasculitis. A meta-analysis was conducted to identify the associations between IL6 rs1800795 (-174 G/C) polymorphisms and vasculitis. A total of 13 studies involving 1,294 vasculitis patients and 1,594 controls were considered in the meta-analysis. There were significant associations between IL6 rs1800795 polymorphisms and vasculitis in allele contrast, dominant genetic model, and heterozygote vs. dominant homozygote comparison (OR 0.80, 95% CI 0.67-0.94, P =0.009 and OR 0.76, 95% CI 0.63-0.92, P =0.005, respectively). In subgroup analysis based on subtype, there were significant associations between IL6 polymorphisms and susceptibility in large and medium vessel vasculitis, but not in small and variable vessel vasculitis. The GC genotype of IL6 rs1800795 was suggested by the analyses to be related to low prevalence of vasculitis, especially for large and medium vessels.